2007
DOI: 10.1186/1472-6882-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Mistletoe lectin is not the only cytotoxic component in fermented preparations of Viscum album from white fir (Abies pectinata)

Abstract: BackgroundPreparations of mistletoe (Viscum album) are the form of cancer treatment that is most frequently used in the complementary medicine. Previous work has shown that these preparations are able to exert cytotoxic effects on carcinoma cells, the extent of which might be influenced by the host tree species and by the content of mistletoe lectin.MethodsUsing colorimetric assays, we have now compared the cytotoxic effects of Viscum album preparations (VAPs) obtained from mistletoe growing on oak (Quercus ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 11 publications
(8 reference statements)
1
33
0
2
Order By: Relevance
“…They all agree on this point that mistletoe extracts exhibit substantial cytotoxic effects in vitro and none of the studies reported growth stimulation and proliferation of tumor cell lines [50–62]. Viscum liquidambaricolum and Viscum coloratum are known as Korean mistletoes which belong to Loranthaceae family and have been used as a traditional medicine in Korea.…”
Section: Preclinical Studiesmentioning
confidence: 93%
“…They all agree on this point that mistletoe extracts exhibit substantial cytotoxic effects in vitro and none of the studies reported growth stimulation and proliferation of tumor cell lines [50–62]. Viscum liquidambaricolum and Viscum coloratum are known as Korean mistletoes which belong to Loranthaceae family and have been used as a traditional medicine in Korea.…”
Section: Preclinical Studiesmentioning
confidence: 93%
“…Therefore, one of the objectives of immunological interventions is activation of effective mechanisms such as maturation of dendritic cells (DCs) [ 2 , 3 ]. There is some evidence that mistletoe lectins stimulate maturation and activation of DCs [ 4 , 5 ], possibly inducing cytotoxic effects [ 6 ]. Lymph node metastasis is seen in accordance with the inability of DCs due to the undifferentiated tumor to maturate, hence providing a peripheric kind of tolerance.…”
Section: Introductionmentioning
confidence: 97%
“…The half-maximal inhibitory concentration (IC 50 ) of lead in cell growth was determined using a dose-response logistic model that has been widely used in toxicological, biological, and pharmacological studies (Eggenschwiler et al 2007;Beckon et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…With the purpose of estimating the IC 50 for Pb of both consortia studied here, the results of Fig. 4 were adjusted to the logistic model of dose-response (Eggenschwiler et al 2007), represented by…”
Section: Biogenic Sulfide Production Kineticsmentioning
confidence: 99%